2013
DOI: 10.1371/journal.pone.0055967
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure, Diet, and Thermoregulation on Fecal Glucocorticoid Measures in Wild Bears

Abstract: We examined fecal glucocorticoid (fGC) measures of nutrition and thermoregulatory demands on wild bears in Glacier National Park, Montana, and assessed how these measures changed in samples left in the field. Both ambient temperature and exposure can impact thermoregulation and sample degradation. Bear diets vary markedly with season, affecting body condition and thus fGC. We collected fecal samples during September and October, 2001, when ambient temperatures ranged from 30°C to −5°C. We collected half of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 21 publications
(28 reference statements)
1
45
0
Order By: Relevance
“…However, a study of grizzly bear ( Ursus arctos horribilis ) and American black bear ( Ursus americanus ) scat reported decreased GCM in response to precipitation (Stetz et al. ). This effect was attributed to steroid metabolite degradation in response to increased water on fecal samples, which could also account for our observed pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study of grizzly bear ( Ursus arctos horribilis ) and American black bear ( Ursus americanus ) scat reported decreased GCM in response to precipitation (Stetz et al. ). This effect was attributed to steroid metabolite degradation in response to increased water on fecal samples, which could also account for our observed pattern.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study on bears found that higher quality diets were associated with lower GCMs, identifying a nutritional influence on GCM concentration measured in fecal samples (Stetz et al. ). However, as we have shown, multiregional comparisons of GCM concentration between populations with access to different types or quality of food and different climatic conditions can be difficult to interpret, as changes in both dietary composition and climate may influence hormone metabolite concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did observe initial declines in some but not all subsamples during the first 24 h after defecation, we also noted marked and consistent increases at exposure times of 3 d to 2 wk. Using an RIA assay, Stetz et al (2013) Crossey et al 2018). We interpret these inconsistencies as strong support for both assay-and species-dependent effects on metabolite stability (Palme 2019), as well as possibly for additional external factors such as gut and environmental bacteria.…”
Section: Discussionmentioning
confidence: 87%
“…It also showed the lowest tendency to detect unusually high fGCM concentrations among the baseline samples. While we are aware of multiple validations for RIA systems for measuring fGCM concentrations in brown bears (Hunt and Wasser 2003;Stetz et al 2013;White et al 2015), we are not aware of any published validations for EIA systems. EIAs may be beneficial in comparison with RIAs because they do not require the handling of radioactive markers (Sheriff et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, exposure to different temperatures and humidity treatments had complex effects on the fGCM concentration in faeces of white-tailed deer ( Odocoileus virginianus ; Washburn and Millspaugh, 2002), wild bears ( Ursus spp. ; Stetz et al ., 2013) and jaguars ( Panthera onca ; Mesa-Cruz et al ., 2014). These results highlight the importance of assessing fGCM stability in field conditions in studies using fGCM to monitor wildlife populations.…”
Section: Introductionmentioning
confidence: 99%